The Histone Deacetylase Inhibitor I1 Induces Differentiation of Acute Leukemia Cells With MLL Gene Rearrangements via Epigenetic Modification - Yao, Jingfang; Li, Gentao; Cui, Zihui; Chen, Peilei; Wang, Jinhong; Hu, Zhenbo; Zhang, Lei; Wei, Liuya (Frontiers in Pharmacology, 2022)
Acute leukemia (AL) is characterized by excessive proliferation and impaired differentiation of leukemic cells. AL includes acute myeloid leukemia (AML) and acute lymphoid leukemia (ALL). Previous studies have demonstrated that about 10% of AML and 22% of ALL are mixed lineage leukemia gene rearrangements (MLLr) leukemia. The prognosis of MLLr leukemia is poor and new therapeutics are urgently needed. Differentiation therapy with all-trans-retinoic acid (ATRA) has prolonged the 5-year disease-free survival rate in acute promyelocytic leukemia (APL), a subtype of AML. However, the differentiation therapy has not been effective in other acute leukemia. Here, we aim to explore the cell differentiation effect of the potent HDACs inhibitor, I1, and the possible mechanism on the MLLr-AML and MLLr-ALL cells (MOLM-13, THP-1, MV4-11 and SEM). It is shown that I1 can significantly inhibit the proliferation and the colony-forming ability of MOLM-13, THP-1, MV4-11 and SEM cells by promoting cell differentiation coupled with cell cycle block at G0/G1 phase. We show that the anti-proliferative effect of I1 attributed to cell differentiation is most likely associated with the activation of hematopoietic cell lineage pathway involved in the HDAC inhibition via the acetylation of histone H3 and H4 in both MOLM-13 and THP-1 cells. Our findings suggest that I1, as a chromatin-remodeling agent, could be a potent epigenetic drug to overcome differentiation block in MLLr-AL patients.